2011
DOI: 10.2217/bmm.11.33
|View full text |Cite
|
Sign up to set email alerts
|

Physiogenomic Analysis of CYP450 Drug Metabolism Correlates Dyslipidemia With Pharmacogenetic Functional Status in Psychiatric Patients

Abstract: Aims To investigate associations between novel human cytochrome P450 (CYP450) combinatory (multigene) and substrate-specific drug metabolism indices, and elements of metabolic syndrome, such as low density lipoprotein cholesterol (LDLc), high density lipoprotein cholesterol (HDLc), triglycerides and BMI, using physiogenomic analysis. Methods CYP2C9, CYP2C19 and CYP2D6 genotypes and clinical data were obtained for 150 consecutive, consenting hospital admissions with a diagnosis of major depressive disorder an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…In a pilot study of psychiatric inpa-tients, we found very high rates of gene alterations compared with a cardiovascular population using a combinatory approach [38]. Our clinical applications study demonstrates that combinatory and drug-specific analyses yielded more significant correlations with clinical measures of metabolic syndrome than did any single gene index [39]. …”
mentioning
confidence: 83%
“…In a pilot study of psychiatric inpa-tients, we found very high rates of gene alterations compared with a cardiovascular population using a combinatory approach [38]. Our clinical applications study demonstrates that combinatory and drug-specific analyses yielded more significant correlations with clinical measures of metabolic syndrome than did any single gene index [39]. …”
mentioning
confidence: 83%
“…While most of these isozymes are known from their involvement in hepatic xenobiotic metabolism, it is important to note that some of them are also expressed in specific brain regions (Ghosh et al 2011;Voirol et al 2000;Gilbert et al 2003). Interestingly, functionally relevant polymorphisms of RA-degrading CYP450 isozymes have recently been linked with major depression and response to antidepressant treatment (Sim et al 2010;Ruano et al 2011). Most interestingly in this context is a study recently published by Persson and colleagues (Persson et al 2014), demonstrating hippocampal atrophy and depressive-like symptoms in a mouse model expressing the human CYP2C19 gene.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report, we had examined associations between CYP450 combinatory geno-types and dyslipidemia in a subcohort of this patient population [39]. Altogether, our results show that CYP450 genotyping and corresponding quantitative indices of pharmacogenetic functional status have potential clinical utility in psychiatry for preventing iatrogenic effects of psychotropic treatment that deleteriously increase utilization of psychiatric services and compromise the quality of care.…”
Section: Discussionmentioning
confidence: 65%
“…These drug metabolism indices were developed previously for multigene CYP450 combinatorial genotyping, and are modified here for a single gene, CYP2D6 [37,39]. Quantitative measures explaining CYP2D6 liver enzyme capacity and deviations from population averages simplify statistical procedures.…”
Section: Methodsmentioning
confidence: 99%